Single-component heat-conducting flame-retardant organic silicon adhesive and preparation method thereof
Thermal conduction of RTV-1 silicone rubber is solved by combining components such as α,ω-dihydroxypolydimethylsiloxane, modified alumina and dithiopyrophosphate in thermally flame-retardant organic silicone adhesives The problems of poor performance and low flame retardant efficiency have achieved high thermal conductivity and high flame retardant adhesives, suitable for thermal bonding and sealing applications of electronic and electrical appliances.
Patent Information
- Application Number
- CN202411638007.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
AI Technical Summary
The existing RTV-1 silicone rubber has poor thermal conductivity, and the flame retardant efficiency of conventional flame retardant fillers affects the mechanical properties and thermal conductivity of adhesives, and cannot meet the demand for high thermal conductivity and high flame retardancy of electronic and electrical products.
Using a single-component thermally flame-retardant organic silicone adhesive, it is made of α,ω-dihydroxypolydimethylsiloxane, dimethylsilicone, modified alumina composite powder with different particle sizes and dithiopyrophosphate, The combination of graphene oxide and molybdenum disulfide is used to build a collaborative flame retardant system to improve thermal conductivity and flame retardant performance.
It realizes excellent thermal conductivity and flame retardant properties of thermally conductive and flame retardant silicone sealant, improves its strength and bonding properties, and is suitable for the thermally conductive and flame retardant sealing field of electronic and electrical appliances, meeting the market's high thermal conductivity, high flame retardant and high performance adhesives need.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sealants, and in particular relates to a single-component heat-conductive flame-retardant organic silicone adhesive and a preparation method thereof. Background Art
[0002] RTV-1 silicone rubber has poor thermal conductivity and cannot meet the needs of electronic components for thermal conductivity and heat dissipation of bonding and sealing components. In order to improve the thermal conductivity of RTV-1 silicone rubber, researchers generally use alumina of different particle sizes as thermal conductive fillers to prepare thermal conductive adhesives. However, these fillers are generally inorganic fillers with low thermal conductivity and large addition amounts. In addition, the flame retardant fillers currently used in common applications have a single flame retardant element and cannot build an efficient synergistic flame retardant system. The flame retardant performance is average, and the addition of flame retardants may affect the mechanical properties and thermal conductivity of the adhesive. With the development of the economy, the widespread popularization of electronic and electrical products, and the increasing attention of the people to the safety of their own lives and property, ordinary thermal conductive adhesives are increasingly unable to meet market demand, and the development of high thermal conductivity, high flame retardancy and high performance adhesives has become a problem that researchers pay more attention to. Patent CN117946618A discloses a thermally conductive alcohol-type silicone sealant and a preparation method thereof. After curing, the sealant has excellent thermal conductivity, and has the advantages of good adhesion, high strength, aging resistance, and a long shelf life. However, it does not have flame retardant properties, which affects its further application in the market. Conventional addition of flame retardants has found that its mechanical properties, bonding properties, thermal conductivity, etc. have declined, and the flame retardant effect is not good. Summary of the invention
[0003] In view of this, in order to solve the above-mentioned technical problems, the purpose of the present invention is to provide a one-component thermally conductive flame-retardant organic silicone adhesive and a preparation method thereof. The thermally conductive flame-retardant organic silicone sealant provided by the present invention has excellent thermal conductivity and flame retardant properties after curing, and has high strength and excellent bonding properties.
[0004] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows:
[0005] The present invention provides a one-component heat-conductive flame-retardant organic silicone adhesive, which is prepared from the following raw materials in parts by weight:
[0006] 100 parts by weight of α,ω-dihydroxypolydimethylsiloxane;
[0007] 50-150 parts by weight of dimethyl silicone oil;
[0008]
[0009] Preferably, the heat-conductive flame-retardant silicone sealant provided by the present invention comprises 100 parts by weight of α,ω-dihydroxy polydimethylsiloxane, wherein the kinematic viscosity of the α,ω-dihydroxy polydimethylsiloxane is preferably 750 to 5000 mm 2 / s, the present invention can use one type of α, ω-dihydroxy polydimethylsiloxane with a single viscosity, or can use several types of α, ω-dihydroxy polydimethylsiloxane with different viscosities in combination.
[0010] Preferably, the heat-conductive flame-retardant organic silicone sealant provided by the present invention further comprises 50 to 150 parts by weight of dimethyl silicone oil, more preferably 100 to 120 parts, wherein the kinematic viscosity of the dimethyl silicone oil is preferably 100 to 350 mm 2 In the present invention, the dimethyl silicone oil mainly plays a plasticizing role and can improve the extrusion performance of the sealant.
[0011] Preferably, the thermally conductive alcohol-type silicone sealant provided by the present invention also includes 1200-1800 parts by weight of thermally conductive powder, more preferably 1400-1600 parts, wherein the thermally conductive powder is a composite powder of aluminum oxide with different particle sizes, more preferably a composite powder of aluminum oxide with different particle sizes modified by fatty acid, stearic acid or hexamethyldisilazane; the composite mass ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 25-40:20-30:5-15:1.5-2:1, and the more preferred ratio is 30-35:24-27:9-12:1.6-1.8:1. In the present invention, the thermally conductive powders of different particle sizes are compounded mainly to increase the packing density of the thermally conductive powder particles, form a more effective thermal conductive channel, and give full play to the thermal conductive effect of the thermally conductive powder.
[0012] Preferably, the thermally conductive alcohol-type silicone sealant provided by the present invention also includes 100 to 500 parts by weight of a flame retardant, more preferably 200 to 350 parts, wherein the flame retardant is a compound powder of dithiopyrophosphate, graphene oxide and molybdenum disulfide, and the compounding mass ratio is 1:1 to 4:3 to 6, and more preferably the ratio is 1:2 to 3:4 to 5; more preferably, the graphene oxide and molybdenum disulfide are modified by one or more of fatty acid, stearic acid or silane coupling agent, respectively. In the present invention, the compounding of dithiopyrophosphate, graphene oxide and molybdenum disulfide is mainly to build a more effective synergistic flame retardant system and improve the flame retardant efficiency.
[0013] Preferably, the thermally conductive alcohol-type silicone sealant provided by the present invention also includes 30 to 80 parts by weight of a cross-linking agent, more preferably 40 to 60 parts by weight, wherein the cross-linking agent is a compound reagent of methyltrimethoxysilane and vinyltrimethoxysilane, wherein the compounding mass ratio of methyltrimethoxysilane to vinyltrimethoxysilane is 1 to 5:1, more preferably 2 to 3:1.
[0014] Preferably, the thermally conductive alcohol-based silicone sealant provided by the present invention further comprises 5 to 20 parts by weight of a tackifier, more preferably 9 to 15 parts by weight, wherein the tackifier is any one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and (3-glycidoxypropyl)methyldiethoxysilane.
[0015] Preferably, the heat-conducting alcohol-based silicone sealant provided by the present invention further comprises 0.5 to 5 parts by weight of a catalyst, more preferably 1 to 3 parts by weight, and more preferably 1 to 2 parts by weight. The catalyst is a titanate chelate, more preferably one or a mixture of diisopropoxytitanium (bisacetoethyl ester) and 1,3-propanedioxytitanium bis(ethyl acetoacetate) (acetylacetone).
[0016] The present invention also provides a method for preparing the above-mentioned one-component thermally conductive flame-retardant organic silicone adhesive, comprising the following steps:
[0017] 1) Add α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, thermal conductive powder and flame retardant to a high-speed dispersing planetary machine, heat to 100-130°C, stir in vacuum for 120-180 minutes, and then cool to 20-50°C;
[0018] 2) adding a cross-linking agent to the mixture in 1) and stirring under vacuum for 10 to 20 minutes;
[0019] 3) Add a tackifier and a catalyst to the mixture in 2), stir under vacuum for 30 to 60 minutes, and mix well to obtain the above-mentioned one-component thermally conductive flame-retardant organic silicone adhesive.
[0020] Preferably, in the preparation method of the present invention, the vacuum degree is controlled at -0.09 to -0.1 MPa, the dispersion speed of the high-speed dispersion planetary machine is preferably 200 to 700 r / min, more preferably 400 to 500 r / min; the stirring speed is preferably 5 to 50 r / min, more preferably 10 to 20 r / min, so as to achieve full mixing of the components of the sealant and uniform stirring. After the stirring is completed, the temperature is lowered to ≤50°C, preferably 30 to 40°C.
[0021] Preferably, in the preparation method of the present invention, the temperature of the step 2) is controlled below 50° C. during the entire process to avoid cross-linking caused by excessively high temperature, thereby further ensuring the quality and performance of the adhesive.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a thermally conductive flame-retardant silicone sealant, which adopts a flame retardant and alumina of different particle sizes to compound, effectively avoiding the problem of single flame-retardant component and low flame-retardant efficiency of traditional thermally conductive adhesives, and graphene oxide and molybdenum disulfide have high thermal conductivity and unique nano-layered structure, which not only makes the sealant have excellent flame retardant properties, but also improves the thermal conductivity of the thermally conductive adhesive and its mechanical properties. The thermally conductive flame-retardant silicone sealant prepared by this method not only has excellent thermal conductivity and flame retardant effect, but also has high strength, can be widely used in the field of thermal conductive bonding and sealing of electronic appliances, effectively meet the thermal conductivity requirements and fire safety of electronic appliances, and has broad market application prospects. In addition, the preparation method provided by the present invention is simple, convenient and efficient, and is easy to industrialize and mass produce. DETAILED DESCRIPTION
[0023] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operation processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] The experimental methods and conditions used in the following examples are conventional methods and conditions unless otherwise specified. The materials, reagents or instruments used in the examples are commercially available or prepared by conventional methods unless otherwise specified.
[0025] The thermally conductive flame-retardant silicone sealant of the present invention is added with the above-mentioned components and the contents of various components are adjusted to make them interact with each other, so that the sealant not only has excellent thermal conductivity and flame retardant properties, but also has high strength. The reaction conditions reflected in the content of the present invention are all capable of achieving the reaction and obtaining products with the expected effects. In order to further understand the present invention, the thermally conductive flame-retardant silicone sealant and the preparation method thereof provided by the present invention are described below in conjunction with some embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0026] The modification involved in the present invention is a conventional powder modification method in the art. For example, the modification method using stearic acid, fatty acid or silane coupling agent as a modifier can be used as an example: take a suspension of powder, add 3.0% (based on the dry basis weight of powder) of modifier at 70°C for surface modification for 30 minutes, and then filter the modified semi-finished product and dry it; when the moisture is dried to 0.8%, crush and sieve the sample to obtain the modified powder. The above is an exemplary modification method. The modification method using stearic acid, fatty acid and silane coupling agent as modifiers in the field is not limited to this one. Other modification methods known to those skilled in the art are also applicable to the present invention, and will not be described in detail due to space reasons. The purpose of the modification is to make the powder and the system have better compatibility and allow the powder to better play its role in the system. It does not constitute an essential impact on the overall scheme and effect of the present invention.
[0027] The preparation method of the heat-conductive flame-retardant organic silicone sealant of the present invention comprises: A) adding α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, heat-conductive powder and flame retardant in a high-speed dispersing planetary machine, heating to 100-130° C., vacuum stirring for 120-180 minutes, and then cooling to 20-50° C.;
[0028] B) adding a crosslinking agent to the mixture in A) and stirring under vacuum for 10 to 20 minutes;
[0029] C) Adding a tackifier and a catalyst to the mixture in B), stirring under vacuum for 30 to 60 minutes, and mixing evenly to obtain the above-mentioned sealant.
[0030] Example 1
[0031] Add kinematic viscosity of 2000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 30:25:10:1.6:1) and flame retardant (the compounding ratio of dithiopyrophosphate, graphene oxide and molybdenum disulfide is 1:3:5, wherein graphene oxide and molybdenum disulfide are modified by fatty acid and silane coupling agent), the temperature is raised to 110°C, vacuumed to a vacuum degree of -0.09MPa, stirred for 150min, the dispersion speed is 500r / min, the stirring speed is 20r / min, and then the temperature is reduced to 45°C. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-aminopropyltriethoxysilane is selected as the viscosity enhancer) and the catalyst (di(isopropoxy)bis(ethyl acetoacetate)titanium is selected as the catalyst) to the above mixture, vacuum stir for 45 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 1.
[0032] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the performance data results are shown in Table 11.
[0033] Table 1 Data table of components and contents of thermally conductive flame-retardant organic silicon sealant in this embodiment
[0034]
[0035] Example 2
[0036] Add kinematic viscosity of 2000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 35:27:12:1.8:1) and flame retardant (the compounding ratio of dithiopyrophosphate, graphene oxide and molybdenum disulfide is 1:4:6, wherein graphene oxide and molybdenum disulfide are modified with fatty acid and silane coupling agent), the temperature is raised to 110°C, vacuumed to a vacuum degree of -0.09MPa, stirred for 150min, the dispersion speed is 500r / min, the stirring speed is 20r / min, and then the temperature is reduced to 45°C. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 4:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-aminopropyltriethoxysilane is selected as the viscosity enhancer) and the catalyst (di(isopropoxy)bis(ethyl acetoacetate)titanium is selected as the catalyst) to the above mixture, vacuum stir for 45 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 2, and the performance data is shown in Table 11.
[0037] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0038] Table 2 Data table of component contents of thermally conductive flame-retardant organic silicon sealant in this embodiment
[0039]
[0040]
[0041] Example 3
[0042] Add kinematic viscosity of 2000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 25:24:6:1.5:1) and flame retardant (the compounding ratio of dithiopyrophosphate, graphene oxide and molybdenum disulfide is 1:2:5, wherein graphene oxide and molybdenum disulfide are modified with fatty acid and silane coupling agent), the temperature is raised to 110°C, vacuumed to a vacuum degree of -0.09MPa, stirred for 150min, the dispersion speed is 500r / min, the stirring speed is 20r / min, and then the temperature is reduced to 45°C. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-glycidyloxypropyltrimethoxysilane and (3-glycidoxypropyl)methyldiethoxysilane as viscosity enhancers, the mass ratio is 2:1) and the catalyst (1,3-propylenedioxybis(ethyl acetoacetate)titanium as the catalyst) to the above mixture, vacuum stir for 45 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 3, and the performance data is shown in Table 11.
[0043] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0044] Table 3 Data table of component contents of thermally conductive flame-retardant organic silicon sealant in this embodiment
[0045]
[0046]
[0047] Example 4
[0048] Add kinematic viscosity of 1000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 350mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 35:30:15:1.5:1) and flame retardant (the compounding ratio of dithiopyrophosphate, graphene oxide and molybdenum disulfide is 1:2:4, wherein graphene oxide and molybdenum disulfide are modified with fatty acid and silane coupling agent), the temperature is raised to 110°C, vacuumed to a vacuum degree of -0.09MPa, stirred for 150min, the dispersion speed is 500r / min, the stirring speed is 20r / min, and then the temperature is reduced to 45°C. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane are used as viscosity enhancers, with a mass ratio of 2:1) and the catalyst (di(isopropoxy)bis(ethyl acetoacetate)titanium is used as the catalyst) to the above mixture, vacuum stir for 60 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 4, and the performance data is shown in Table 11.
[0049] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0050] Table 4 Data table of component contents of thermally conductive flame-retardant organic silicon sealant in this embodiment
[0051]
[0052] Example 5
[0053] Add kinematic viscosity of 1000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 35:27:10:2:1) and flame retardant (the compounding ratio of dithiopyrophosphate, graphene oxide and molybdenum disulfide is 1:3:6, wherein graphene oxide and molybdenum disulfide are modified with fatty acid and silane coupling agent), the temperature is raised to 110°C, vacuumed to a vacuum degree of -0.09MPa, stirred for 150min, the dispersion speed is 500r / min, the stirring speed is 20r / min, and then the temperature is reduced to 45°C. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-aminopropyltriethoxysilane is selected as the viscosity enhancer) and the catalyst (1,3-propylenedioxybis(ethyl acetoacetate)titanium is selected as the catalyst) to the above mixture, vacuum stir for 30 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 5, and the performance data is shown in Table 11.
[0054] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0055] Table 5 Data table of component contents of thermally conductive flame-retardant organic silicon sealant in this embodiment
[0056]
[0057] Comparative Example 1
[0058] Add kinematic viscosity of 2000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle size of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 30﹕25﹕10﹕1.6﹕1) and flame retardant (replaced by thermal conductive powder), heat to 110℃, evacuate to a vacuum degree of -0.09MPa, stir for 150min, dispersing speed of 500r / min, stirring speed of 20r / min, and then cool to 45℃. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-aminopropyltriethoxysilane is selected as the viscosity enhancer) and the catalyst (di(isopropoxy)bis(ethyl acetoacetate)titanium is selected as the catalyst) to the above mixture, vacuum stir for 45 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 6, and the performance data is shown in Table 11.
[0059] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0060] Table 6 Data table of component contents of thermally conductive flame-retardant organic silicon sealant in this embodiment
[0061]
[0062] Comparative Example 2
[0063] Add kinematic viscosity of 2000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle size of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 30:25:10:1.6:1) and flame retardant (only dithiopyrophosphate is used as flame retardant), heat to 110℃, evacuate to a vacuum degree of -0.09MPa, stir for 150min, dispersing speed is 500r / min, stirring speed is 20r / min, and then cool to 45℃. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-aminopropyltriethoxysilane is selected as the viscosity enhancer) and the catalyst (di(isopropoxy)bis(ethyl acetoacetate)titanium is selected as the catalyst) to the above mixture, vacuum stir for 45 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 7, and the performance data is shown in Table 11.
[0064] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0065] Table 7 Data table of components and contents of thermally conductive flame-retardant organic silicone sealant in this embodiment
[0066]
[0067] Comparative Example 3
[0068] Add kinematic viscosity of 2000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 30:25:10:1.6:1) and flame retardant (only graphene oxide is used as flame retardant), heat to 110℃, evacuate to a vacuum degree of -0.09MPa, stir for 150min, dispersing speed at 500r / min, stirring speed at 20r / min, and then cool to 45℃. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-aminopropyltriethoxysilane is selected as the viscosity enhancer) and the catalyst (di(isopropoxy)bis(ethyl acetoacetate)titanium is selected as the catalyst) to the above mixture, vacuum stir for 45 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 8, and the performance data is shown in Table 11.
[0069] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0070] Table 8 Data table of components and contents of thermally conductive flame retardant organic silicon sealant in this embodiment
[0071]
[0072]
[0073] Comparative Example 4
[0074] Add kinematic viscosity of 2000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle size of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 30:25:10:1.6:1) and flame retardant (only molybdenum disulfide is used as flame retardant), heat to 110℃, evacuate to -0.09MPa, stir for 150min, dispersing speed is 500r / min, stirring speed is 20r / min, and then cool to 45℃. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (γ-aminopropyltriethoxysilane is selected as the viscosity enhancer) and the catalyst (di(isopropoxy)bis(ethyl acetoacetate)titanium is selected as the catalyst) to the above mixture, vacuum stir for 45 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 9, and the performance data is shown in Table 11.
[0075] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0076] Table 9 Data table of component contents of thermally conductive flame-retardant organic silicone sealant in this embodiment
[0077]
[0078] Comparative Example 5
[0079] Add kinematic viscosity of 2000mm in high-speed planetary dispersing machine 2 / s α, ω-dihydroxy polydimethylsiloxane, kinematic viscosity 100mm 2 / s dimethyl silicone oil, thermal conductive powder (the compounding ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 30:25:10:1.6:1) and flame retardant (the compounding ratio of dithiopyrophosphate, graphene oxide and molybdenum disulfide is 1:3:5, wherein graphene oxide and molybdenum disulfide are modified by fatty acid and silane coupling agent), the temperature is raised to 110°C, vacuumed to a vacuum degree of -0.09MPa, stirred for 150min, the dispersion speed is 500r / min, the stirring speed is 20r / min, and then the temperature is reduced to 45°C. Then add the crosslinking agent (the compounding mass ratio of methyltrimethoxysilane and vinyltrimethoxysilane is 3:1), vacuum stir for 15 minutes, and control the temperature below 50°C during the whole process; finally, add the viscosity enhancer (replaced with dimethyl silicone oil) and catalyst (select di(isopropoxy)bis(ethyl acetoacetate)titanium as catalyst) to the above mixture, vacuum stir for 45 minutes, stir evenly under vacuum conditions and then discharge. The specific mass ratio is shown in Table 10, and the performance data is shown in Table 11.
[0080] The performance of the obtained thermally conductive flame retardant silicone sealant was measured, and the results are shown in Table 11.
[0081] Table 10 Data table of component contents of thermally conductive flame-retardant organic silicone sealant in this embodiment
[0082]
[0083] Test Case
[0084] The adhesives obtained in the above embodiments and comparative examples were subjected to performance tests. The specific test methods and results are as follows:
[0085] Test method for surface drying time: refer to GB / T13477.5-2002 method for testing
[0086] Hardness test method: According to GB / T 531.1-2008 standard, use Shore hardness tester for testing.
[0087] Breaking strength and breaking elongation: tested in accordance with GB / T 528-2009 standard using a universal testing machine.
[0088] Thermal conductivity
[0089] High temperature aging: Use a 10*10* polytetrafluoroethylene mold to prepare a sealant film. After curing at room temperature for 7 days, take out the film and place it in a 110°C blast oven. Take it out after 24 hours and observe its yellowing.
[0090] Adhesion after hot pressing and cold drawing: Tested according to GB / T13477.13-2002 method
[0091] Adhesion after UV irradiation: The UV test chamber should comply with the provisions of 5.12.1 of JC / T 485-2007. The light should be continuously irradiated for 300 hours without immersion in water. The surface temperature of the specimen should be 40±5℃ during the irradiation period. After the irradiation, the test should be carried out in accordance with the provisions of GB / T13477.10-2017. After the test, the specimen should be inspected in accordance with 7.1 of GB / T22083-2008, and the damage should be evaluated in accordance with 7.3 of this standard.
[0092] Flame retardant grade: tested according to UL94 method.
[0093] Table 11 Performance data of each implementation case
[0094]
[0095]
[0096] In Comparative Example 1, the flame retardant is replaced by thermal conductive powder, the tensile strength decreases, the elongation at break decreases, and the flame retardant performance deteriorates, indicating that after adding the flame retardant, the mechanical properties and flame retardant properties of the thermal conductive flame retardant silicone sealant are effectively enhanced; in Comparative Examples 2, 3 and 4, only dithiopyrophosphate, graphene oxide and molybdenum disulfide are added as flame retardants, respectively, and the flame retardant grades of the three comparative examples are all V1, which is similar to Comparative Example 1. It is shown that when dithiopyrophosphate, graphene oxide and molybdenum disulfide are added as single flame retardants, the flame retardant properties of the sealant cannot be effectively improved. However, it can be seen from the examples that when the three are added at the same time in a certain proportion, the flame retardant grade of the sealant reaches V0, indicating that the composite use of the three has a better flame retardant effect, which is mainly due to the fact that during the combustion process, graphene oxide can provide a carbon source, dithiopyrophosphate can promote the carbonization of the sealant, and molybdenum disulfide has a good physical barrier effect and catalytic carbonization ability. The synergistic effect between the three can effectively improve the flame retardant properties of the sealant. Moreover, the mechanical properties of Comparative Example 2 are poor, while the mechanical properties of Comparative Examples 3 and 4 are improved, but still poor compared with the examples, indicating that dithiopyrophosphate does not have the effect of improving the mechanical properties of the sealant, while graphene oxide and molybdenum disulfide have the effect of improving the mechanical properties of the sealant, which is mainly due to the fact that both graphene oxide and molybdenum disulfide have a certain two-dimensional layered nanostructure, which can produce a certain force between the siloxane cross-linked network and the thermal conductive powder in the sealant, thereby improving the mechanical properties of the sealant. It can be seen from Comparative Example 5 that when no tackifier is added, the surface drying time becomes longer, the adhesion of the sealant becomes worse, and the flame retardant and mechanical properties of the sealant remain basically unchanged, indicating that the tackifier in the present invention mainly affects the adhesion of the sealant, and has little effect on the mechanical properties and flame retardant properties.
[0097] Different fillers in the field of sealants will affect the processing technology and the final product effect. If the filler is added in too high a proportion, the viscosity of the glue will be too large, affecting the normal use of the glue. Moreover, if the filler is added in too high a proportion, the relative addition amount of α, ω-dihydroxy polydimethylsiloxane, crosslinking agent and tackifier will be reduced, thereby making the mechanical properties, aging resistance and bonding properties of the glue worse. The various formulas of the present invention have been verified by calculation and experiment, and graphene oxide and molybdenum disulfide are used. These two flame retardants not only have good flame retardant effects, but also can improve the mechanical properties of the material, and their thermal conductivity is not worse than that of thermal conductive powder. Therefore, the compounded flame retardant has a flame retardant effect in the adhesive system and also has an enhanced effect, and can also play a role of heat conduction together with thermal conductive powder.
[0098] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. Other variations and modifications are possible without exceeding the technical solutions described in the claims.
Claims
1. A one-component thermally conductive flame-retardant organic silicone adhesive, characterized in that: It is prepared from the following raw materials in parts by weight:
2. A one-component thermally conductive flame-retardant organic silicone adhesive according to claim 1, characterized in that: The kinematic viscosity of the α,ω-dihydroxy polydimethylsiloxane is 750-5000 mm 2 / s.
3. The one-component thermally conductive flame-retardant organic silicone adhesive according to claim 1, characterized in that: The kinematic viscosity of the dimethyl silicone oil is 100 to 350 mm 2 / s.
4. The one-component thermally conductive flame-retardant organic silicone adhesive according to claim 1, characterized in that: The thermal conductive powder is a composite powder of aluminum oxide with different particle sizes, and the composite ratio of aluminum oxide with particle sizes of 0.2-0.7μm, 0.6-1.5μm, 2.3-11.5μm, 27-41μm and 78-105μm is 25-40:20-30:5-15:1.5-2:1; the aluminum oxide is unmodified aluminum oxide, or aluminum oxide modified by fatty acid, stearic acid or hexamethyldisilazane.
5. The one-component thermally conductive flame-retardant organic silicone adhesive according to claim 1, characterized in that: The flame retardant is a compound powder of dithiopyrophosphate, graphene oxide and molybdenum disulfide, and the compounding mass ratio is 1:1-4:3-6; wherein the graphene oxide and molybdenum disulfide are respectively unmodified, or modified by one or more of fatty acid, stearic acid or silane coupling agent.
6. The one-component thermally conductive flame-retardant organic silicone adhesive according to claim 1, characterized in that: The crosslinking agent is a compound reagent of methyltrimethoxysilane and vinyltrimethoxysilane, wherein the compounding mass ratio of methyltrimethoxysilane to vinyltrimethoxysilane is 1 to 5:
1.
7. The one-component thermally conductive flame-retardant organic silicone adhesive according to claim 1, characterized in that: The adhesion promoter is any one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and (3-glycidoxypropyl)methyldiethoxysilane.
8. The one-component thermally conductive flame-retardant organic silicone adhesive according to claim 1, characterized in that: The catalyst is a phthalate chelate.
9. The one-component thermally conductive flame-retardant organic silicone adhesive according to claim 1, characterized in that: The catalyst is one of diisopropoxytitanium (ethyl bisacetoacetate) and 1,3-propanedioxytitanium bis (ethyl acetoacetate) (acetylacetone) or a mixture of the two.
10. A method for preparing the one-component thermally conductive flame-retardant organic silicone adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Add α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, thermal conductive powder and flame retardant to a high-speed dispersing planetary machine, heat to 100-130°C, stir in vacuum for 120-180 minutes, and then cool to 20-50°C; 2) adding a cross-linking agent to the mixture in 1) and stirring under vacuum for 10 to 20 minutes; 3) Adding a tackifier and a catalyst to the mixture in 2), stirring the mixture under vacuum for 30 to 60 minutes, and mixing the mixture evenly to obtain a single-component thermally conductive flame-retardant organic silicone adhesive.
Citation Information
Patent Citations
Heat-conducting alcohol type organic silicon sealant and preparation method thereof
CN117946618A